Influence of Green Open Spaces (GOS) on bird composition and abundance in Kendari City, Southeast Sulawesi, Indonesia - SITTI WIRDHANA AHMAD; LA ODE MUHAMMAD ERIF; MUKHSAR MUKHSAR; ADMIYANI SAMBO ADCU; RITA ISNAWATI; ZUKNI INDARWANI; FADILAH FADILAH; ADI KARYA (Society for Indonesian Biodiversity, 2025)
Abstract. Ahmad SW, Erif LOM, Mukhsar, Adcu AS, Isnawati R, Indarwani Z, Fadilah, Karya A. 2025. Influence of Green Open Spaces (GOS) on bird composition and abundance in Kendari City, Southeast Sulawesi, Indonesia. Biodiversitas 26: 5814-5823. One of the negative impacts of shrinking Green Open Spaces (GOS) and urban landscape change is the decline in biodiversity. GOS play a key role in maintaining biodiversity within rapidly expanding cities. In urban areas, GOS such as urban parks serve as habitats for birds despite high human density and altered land cover. Complex and diverse vegetation structures provide better habitat quality, and larger GOS connected to natural habitats tend to support higher bird diversity. This study examined the influence of GOS characteristics, area, vegetation quality, water availability, and connectivity with natural habitats on bird composition and abundance in Kendari City, Southeast Sulawesi, Indonesia. Eight GOS sites were surveyed, recording a total of 48 bird species, including 14 Sulawesi endemics, with total abundance ranging from 208 to 580 individuals per site. Canonical Correspondence Analysis (CCA) indicated that these habitat variables explained 12.33% of the variation in bird community composition, suggesting a weak but ecologically meaningful influence. While generalist species dominated smaller ornamental parks, larger, forest-like sites supported higher species richness and endemic representation. These findings highlight the importance of retaining native vegetation and ensuring water availability in urban planning to enhance bird diversity and support biodiversity-based management strategies.